Growth of {11-22} twins in titanium: A combined experimental and modelling investigation of the local state of deformation - Wilkinson, A; Guo, Y; Abdolvand, H; Britton, T (Elsevier, 2016)
In this work we combine experiments and simulations to study the residual deformation state near twins in titanium at different stages of the complete twin growth process, including the twin tip: (i) far from a grain boundary, (ii) approaching a grain boundary, and (iii) intersecting with a grain boundary. High resolution electron backscatter diffraction (HR-EBSD) was used to characterise the local residual stress state and dislocation density distributions. Schmid factors were calculated from both the global deformation state (i.e. remote loading) and local deformation state (i.e. from high angular resolution EBSD). Crystal plasticity finite element modelling was used to simulate the stress field close to twins during loading and unloading. These simulations indicate that while the magnitudes of the localized stress fields close to twin boundaries are reduced upon removing the far field load, the major features of the stress fields in these regions are dominated by accommodation of the twin and thus persist from the peak load state to the unloaded state. We find a good correlation between the active twin variant and the maximum local Schmid factor, while the external loading (i.e. global Schmid factor) plays a less important role. These findings are useful in determining which twins will grow when a sample is deformed, and this has important implications for in service performance as well as texture evolution during mechanical processing.